DOP036 Ustekinumab for Crohn's disease: a nationwide real-life observational cohort study (ICC case series). (16th January 2018) - Biemans, V; van der Meulen - de Jong, A; van der Woude, C; de Boer, N; Dijkstra, G; Oldenburg, B; Ponsioen, C; Maljaars, P; Haans, J; Pierik, M; Hoentjen, F; ,
Abstract: Background: Ustekinumab (UST) targets the p40 unit of interleukin-12 and interleukin-23 and is approved for treatment of Crohn's disease (CD). The majority of CD patients included in the registration trials are highly selected patients from referral centres, satisfying strict inclusion/exclusion criteria and following detailed protocols that do not accurately reflect routine care. We therefore designed a nationwide cohort (ICC case series) of UST-treated CD patients in order to systematically assess real-life effectiveness and safety. Methods: CD patients who started UST from November 2016 in seven university medical centres were included. We used a predefined follow-up (0-12-24-52-104 weeks) and assessed systematically clinical disease activity (Harvey–Bradshaw (HBI), inflammatory biomarkers (C-reactive protein and faecal calprotectin)), hospital admissions, IBD-related surgery and adverse events. Clinical remission was defined as HBI < 5. Wilcoxon signed-rank test was used. Results: We enrolled 125 CD patients (82 female, mean age 40.2 ± 13.4 years) with a mean disease duration of 14.1 ± 9.9 years. At baseline 67 (53.6%) had a history of IBD-related surgery, 124 (99.2%) had failed at least one biological and 61 (48.8%) had used vedolizumab. 32 (25.6%) patients had stricturing disease, 14 (11.2%) penetrating disease, and 23 (18.4%) perianal disease. Concomitant medication at baseline included corticosteroids ( n = 24), immunosuppressants (thiopurines or methotrexate, IMM, n = 24) and 8 used the combination. The median follow-up was 17.1 (IQR 8–24) weeks. After 12 weeks of treatment, disease activity decreased as indicated by HBI: median 8 (IQR 4–12) vs. 5 (2–9) p < 0.001 and biochemical markers (CRP: median 11 (IQR 4-25) vs. 5 (1–13) p < 0.001, faecal calprotectin median 598 (IQR 275–1607) vs. 393 (142–393) p = 0.002). At week 24, the injection interval was 8 weeks or less in 70.1% of the subjects. No anti-drug antibodies were detected in 29 (23.2%) patients who underwent pharmacokinetic evaluation. UST was discontinued in 17.6% after a median treatment duration of 18.8 (IQR 13–25.5) weeks, 77.3% due to primary non-response and 9.1% due to adverse events including one infusion reaction. Four severe infections requiring hospital admission were reported. Conclusions: Our nation-wide real-life data on UST showed that 45% of CD patients achieved clinical remission at 12 weeks accompanied by a reduction in inflammatory markers. Two serious adverse events required discontinuation of therapy and four severe infections resulting in hospital admission were reported.